ANALISIS PENGARUH PENDIDIKAN ORANG TUA TERHADAP FERTILITAS DI INDONESIA - Faiza Conita Chairiya Harahap; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Fertility is the result of female reproduction. Fertility is a term that describes the number of children born alive. The large number of children born in Indonesia is one of the causes of rapid population growth. The high birth rate is influenced by many factors, one of which is education. The education received by both parents greatly influences the thoughts of both wives and husbands in having children because parents who have higher education tend to be more open-minded. Their minds are more rational so they will take everything into account before acting. This research aims to find out how parents' education influences their choice in the number of children they want to have. The research method used is a qualitative method with data collection techniques through literature study. Researchers collect data through articles and journals which are then read and studied. The results of this research are that education is a factor that has a very significant influence on fertility or birth, especially the wife's education which determines the amount of fertility. Meanwhile, for husband's education, husband's education does not have much influence on fertility.